(untitled) (Swiss Medical Weekly, 2011)
The new paradigm of therapy in rheumatoid arthritis is to aim toward early and complete remission, using a larger use of conventional DMARDs and biologic agents. The present recommendations were established through a consensus to help practitioners in their daily use of those agents, to reflect the current “best practice” in Switzerland.